Identification of Sense of Urgency as Critical Success Factor in Implementation of ERP for Educational Sector of Saudi Arabia: A Case Study - Mohammed R A Siam; Wael Sh. Basri (International Journal of Supply Chain Management, 2017)
Enterprise Resource Planning (ERP) has significant role in operationalization of various activities of organizations in integrated mode. Now, the educational institutions are implementing Enterprise Resource Planning (ERP) practices to gain efficiency and effectiveness in a worldwide competitive environment. This research study highlights the literature on ERP implementation and reveals the sense of urgency as one of the critical success factor for effective and successful implementation of latest technological advancements within higher education institutions of Kingdom of Saudi Arabia. To measure EPR implementation, we have selected a case from Saudi Arabia, and this case will be an evidence of ERP implementation in Saudi Arabia. Project Management is highlighted among various success factors of successful implementation of ERP system in higher educational sector of KSA. This research study is contributing to academic research by providing an empirical evidence to support the theories of CSFs and ERP implementation success.